2019
DOI: 10.1155/2019/2474273
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Gait Stability before and after Cochlear Implantation

Abstract: Background It is known that cochlear implantation may alter the inner ear and induce vestibular disorders. Research Question How does cochlear implantation influence gait stability? Material and Methods. An experimental group of twenty-one subjects scheduled for cochlear implantation underwent gait testing twice, on the day before cochlear implantation (BCI) and three months after cochlear implantation (ACI), using a motion capture system. A control group of 30 age-matched healthy individuals were also tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…Confirming that high GSR values are associated with poor postural control [ 45 , 57 ], a large, negative and significant association was found. This result suggested the GSR is a predictor of falls in the older adult population, as was found in previous studies [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 86%
“…Confirming that high GSR values are associated with poor postural control [ 45 , 57 ], a large, negative and significant association was found. This result suggested the GSR is a predictor of falls in the older adult population, as was found in previous studies [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 86%
“…Authors reported that unilateral CI could alter a previously uncompensated vestibular injury; thus, inducing compensation, greater self-confidence, and improvement in spatial orientation [ 33 , 34 ]. In a recent publication, gait stability was evaluated in 21 patients after CI, finding better parameters than those observed before surgery; the authors report that videonystagmography, vHIT, and VEMP were performed to demonstrate these data, but results are not described in the study; furthermore, these patients did not present vestibular symptoms before implantation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since no patient in our study had a conspicuous result in the Romberg test, it can be concluded that neither preoperatively nor postoperatively was a central lesion present. Kaczmarczyk et al (45) who used the Romberg test to assess gait stability before and after cochlear implantation, also found no increased stance or gait instability postoperatively.…”
Section: Romberg Testmentioning
confidence: 98%